Determinants of Utilization of Home-Based Care in Kisumu County. - Ratori, Erick Enock; Oluoch, Musa; Mwangi, Muthoni (International Journal of Health Sciences, 2024)
Purpose: To examine the factors influencing the utilization of Home-Based Care in Kisumu Central. It examined the influence of predisposing factors, enabling factors, the environment and Health Behaviors on utilization of Home-Based Care. Methodology: This was a mixed research design which employed both qualitative and quantitative methods to examine and characterize the elements that impact the use of home-based care. The study samples consist of 120 respondents selected from among home based care users. The data was collected through structured questionnaires that were self-administered to home-based care users. The collected data was quantitative and analyzed using descriptive and statistical tools like SPSS (version27). The findings were displayed in tables. Descriptive statistics, Bivariate correlation and multivariate regression models were utilized to determine the relationship between the independent and dependent variables. Findings: The study found that predisposing factors, enabling factors, the environment and health behaviors were significant factors influencing the utilization of home-based care in Kisumu Central Sub County with significant p=.000 each. Unique contribution to theory, practice and policy (recommendations): Theory: The study challenges traditional theories by demonstrating that predisposing factors, enabling factors and the environment are more significant than health behaviors in influencing Home-Based Care utilization. Policymakers should implement strategies that target investments in and support for Home Based Care as a vital component of healthcare delivery, particularly for individuals with chronic illnesses and those requiring personalized and accessible care within their homes.